2000
DOI: 10.1002/1097-4644(20001101)79:2<225::aid-jcb60>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear import and DNA binding of human papillomavirus type 45 L1 capsid protein

Abstract: During the life cycle of human papillomaviruses (HPVs), the L1 capsid proteins seem to enter the nucleus twice: once after the virions infect the cells, and later during the productive phase when they assemble the replicated HPV genomic DNA into infectious virions. We established for the high-risk HPV45 that when digitonin-permeabilized HeLa cells were incubated with L1 homopentameric capsomers, the HPV45 L1 protein was imported into the nucleus in a receptor-mediated manner. In contrast, intact capsids were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In accordance with this finding, linear L1 epitopes are continuously detected in Lamp-3 positive compartments late in infection [60]. Previous studies showing that intact HPV capsids exceed the size capacity for transit across the central nuclear pore complex channel had already suggested that disassembly of the viral particle must occur before nuclear import [73,74]. L2 protein is not essential for viral uncoating, as measured by the detection of bromodeoxyuridine-labeled genome after infection with L1-only particles [70].…”
Section: Viral Uncoating and Egress From Endosomessupporting
confidence: 77%
“…In accordance with this finding, linear L1 epitopes are continuously detected in Lamp-3 positive compartments late in infection [60]. Previous studies showing that intact HPV capsids exceed the size capacity for transit across the central nuclear pore complex channel had already suggested that disassembly of the viral particle must occur before nuclear import [73,74]. L2 protein is not essential for viral uncoating, as measured by the detection of bromodeoxyuridine-labeled genome after infection with L1-only particles [70].…”
Section: Viral Uncoating and Egress From Endosomessupporting
confidence: 77%
“…KPNA2 plays a crucial role during viral infections mainly by importing parts of the viral machinery to the nucleus. It has so far been implicated in the shuttling of factors from a variety of viruses such as HIV [76], Epstein-Barr virus [77], polyomavirus [78] and HPV [79][80][81]. Furthermore, KPNA2 has been proposed to hold a role in regulating viral capsid assembly, preventing it from faultily occurring in the cytoplasm [82].…”
Section: Kpna2 Has Been Implicated In a Multitude Of Cellular Processesmentioning
confidence: 99%
“…For example, parvovirus delivers its DNA into the nucleus through karyopherin ␣ and karyopherin ␤ (17). The replication of human papillomavirus is inhibited by antibodies against KPNA2 and KPNB1 (18). Moreover, herpesvirus and adenovirus rely on karyopherins for their nuclear entry (19).…”
mentioning
confidence: 99%